KOMPENSASI DAN KEDISIPLINAN SEBAGAI FAKTOR YANG BERPENGARUH TERHADAP KINERJA DAN KEPUASAN KERJA KARYAWAN BANK - Lita Dwipasari (Jurnal Keuangan dan Perbankan, 2008)
This research was aimed to know the compensation effect and working disciplineas the factor that influenced to job performance and satisfaction. Research population wasofficers of Jatim bank of Malang by using Judment sampling method. The respondents were48 people. The data was analyzed by using Path analyze.The result of this research was thatcompensation given by Jatim Bank of Malang influenced officers job satisfaction indirectly.While the effect of compensation toward officers job performance could not be proved. Thismatter showed officers job performance was not influenced by the compensation given bythe bank. However, it was influenced by the discipline factor of the officers and it was provedempirically in this research.